Stress granules attenuate protein nanoparticle induced osmotic imbalance via membrane potential restoration - Xianrui Song; Wenzhao Zhou; Yuqing Shi; Ying Zhao; Kaili Huang; Yichen Guo; Huanhuan Zhao; Yanqiong Li; Jun Guo (Scientific Reports)
Abstract Stress granules (SGs) are biomolecular condensates formed in response to stress stimuli, and they can alter intracellular protein particles. Here, SG assembly was noted to effectively stabilize intermediate filament tension, intracellular osmolarity, Ca2+ signaling, and membrane potential via protein nanoparticle (PN) and inflammasome inhibition. However, protein particle generation elicited by cytoskeletal depolymerization delays SG maturation because primary SGs form only after exposure to H2O2 and LPS cotreatment, which increases intracellular osmotic pressure. EWSR1 mutation increases intracellular protein nanoparticle-related osmotic pressure, stimulating inflammatory reaction through SG formation blockade. In contrast, TRIM21 knockdown promotes SG prematurity and induces rapid protein nanoparticle-related osmotic pressure recovery through membrane potential stabilization. Our results clarified the critical functions of SGs in response to combined oxidative stress and inflammation, involving transmembrane osmotic pressure and structure regulation through alterations in intracellular protein nanoparticle, Ca2+ signaling, and membrane potential under electrochemical–tension interactions.